Effectiveness of utilizing VCO oil and castor oil on natural creams for dry skin treatment due to environmental factors - Atmanto, D (Journal of physics. Conference series, 2019)
Rapid industrial development can lead to environmental pollution. Bad air environment will cause damage to the skin such as dry skin. Indonesia has biological natural resources such as coconut trees and castor oil plants. Both oils can be used to make skin care due to the impact of heat by the environment. This study aims to determine the effectiveness of using VCO oil from coconut and castor oil in natural creams to treat dry skin. The method of this research is comparing composition variation of VCO oil and castor oil to make natural creams. The experiment was carried out on 10 dry skins of student volunteers. Research using designated randomized group is divided into two groups. Group A is the experimental unit for treatment and group B is a comparison group, with subjects are selected by purposive sampling from a particular population. This study used an 8-experimental design of the initial test until the final test in both groups. The results showed that t count > t table is 2.441> 1.330 so Ho is rejected and HI is accepted at the 0.05 significance level. There are differences in the use of pure coconut oil cream (VCO) and castor oil cream to reduce the smoothness of the skin.